Effects of protection from fishing on the lengths of targeted and non-targeted fish species at the Houtman Abrolhos Islands, Western Australia - Watson, D.; Anderson, M.; Kendrick, G.; Nardi, K.; Harvey, Euan (Inter-Research, 2009)
The effects of fishing and protection on the length of targeted and non-targeted warmtemperateand tropical reef fishes were studied using baited remote underwater stereo-videocameras at the Houtman Abrolhos Islands, Western Australia. Video images were obtained from inside a marine protected area (MPA) and from 3 replicate fished locations within each of 3 island groups. The effects of protection on the lengths of 6 targeted and 4 non-targeted fish species were examined. Five of the 6 targeted fish species were larger inside MPAs than in areas open to fishing (Choerodon rubescens, Lethrinus miniatus, Lethrinus nebulosus, Pagrus auratus and Plectropomus leopardus). Targeted species were, on average, 48 mm (10%) larger inside MPAs than in areas open to fishing. The vast majority of the individuals of C. rubescens, P. auratus and P. leopardus recorded were smaller than their minimum legal size for first capture. For non-targeted species, only 1 of the 4, Coris auricularis, showed an effect of protection, with the mean length of individuals reduced by 85 mm (33%) inside MPAs relative to areas open to fishing. This study demonstrated clear effects of protection from fishing on the size structure of populations of common warm-temperate and tropicalreef fishes.